Antioxidant compounds enhanced the anatomical characteristics of Date Palm (Phoenix dactylifera L.) offshoot leaves under salinity stress. - Shareef, Hussein J; ِAlarab Emad H. A. (Basrah Journal Of Date Palm Research, 2025)
This study was conducted to investigate the protective effects of foliar spraying with antioxidant compounds, including calcium chelate, potassium chelate, salicylic acid, and citric acid (1000 ppm each), on the anatomical characteristics of date palm offshoot leaves under salinity stress (soil electrical conductivity: 14 dS m-1 irrigation water: 4 dS m-1), for both Barhee and Sayer cultivars. The use of antioxidants significantly increased leaf anatomical parameters. Salicylic acid treatment was the most effective, resulting in increased leaf blade thickness, vascular bundle diameter, xylem thickness, phloem thickness, epidermal thickness, and tannin cell density in both cultivars. In contrast, antioxidant treatments generally reduced stomatal density. Furthermore, the Barhee cultivar exhibited consistently superior anatomical responses compared with the Sayer cultivar. These findings demonstrate that exogenous application antioxidant-related compounds can alleviate salinity-induced structural alterations and contribute to improved anatomical adaptation in date palm offshoots..